(untitled) (Research, Society and Development, 2025)
Health education is a fundamental strategic component in the prevention of occupational risks in hospital environments, particularly among nursing professionals who are daily exposed to multiple physical, cognitive, and psychosocial risk factors. Structured educational programs have proven effective in mitigating these risks. This study aims to support healthcare institutions in implementing policies and programs that strengthen professional self-care and preserve the well-being of those on the front lines of hospital care. Studies indicate that combining theoretical, practical, and digital approaches enhances the effectiveness of modifying risk behaviors, strengthening self-care, and preventing physical and emotional complications arising from hospital routines. Moreover, integrating mental health measures, such as burnout prevention, is essential to mitigate the intensity of occupational pain. Emotional exhaustion, depersonalization, and low professional accomplishment are strongly associated with increased chronic pain, fatigue, and reduced quality of care. Practical examples of application include ergonomic workshops in different hospital sectors, mindfulness sessions adapted to professionals’ schedules, programmed breaks with stretching exercises, and digital platforms that record individual and collective team progress. This study synthesizes recent evidence on the effectiveness of structured educational interventions, emphasizing the need for institutional support, continuous evaluation, content personalization, and the integration of mobile technologies.